Creep life prediction of small punch creep testing specimens for service-exposed Cr5Mo using the theta-projection method. (February 2017) - Zheng, Yangyan; Yang, Sisheng; Ling, Xiang
Abstract: In this paper, small punch creep tests under different loads and conventional creep tests with various stresses at 550 °C were conducted on service-exposed Cr5Mo material. The theta-projection and modified theta-projection methods were used to analyze the creep curve and the minimum creep rate. The actual fracture time in the small punch creep test was 377 h, and the theta-projection method predicted a time of 339 h, which represents an error of 10.08%. The predicted time from the modified theta-projection method was 316.25 h, which represents an error of 16.11%. The curves predicted by the two models are similar. The theta-projection method is suitable for applications in small punch creep life analysis. Highlights: The modified θ -projection method was used to analyze the creep curves. The modified θ -projection method is suited for small punch creep tests. The modified θ model can rapidly predict the in-service material's remaining life.